1996
DOI: 10.1002/(sici)1097-0215(19960822)69:4<301::aid-ijc11>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Telomerase activity in human breast cancer and benign breast lesions: Diagnostic applications in clinical specimens, including fine needle aspirates

Abstract: We analysed telomerase activity in normal, benign and malignant breast tissues and in fine needle aspirates by a PCR-based assay. The tissue samples we used in this assay consisted of 20 cryostat sections, I0 pm thick, from each breast biopsy. This method was used to obtain effective extraction from small samples and to confirm the histological identity of the specimen by microscopical examination of serial sections. Fifty-two of 7 I breast carcinomas were positive for telomerase activity, and the intensity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
2

Year Published

1997
1997
2002
2002

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(43 citation statements)
references
References 16 publications
3
38
2
Order By: Relevance
“…Following the development by Kim et al (1994) of an extremely sensitive PCR-based assay, telomerase activity has been found in a large variety of solid tumours, including neuroblastomas (Hiyama et al, 1995a), lung carcinomas (Hiyama et al, 1995b), hepatomas (Tahara et al, 1995a), gastric and colon carcinomas (Chadeneau et al, 1995;Hiyama et al, 1995c;Tahara et al, 1995bLi et al, 1996, breast carcinomas (Hiyama et al, 1996;Sugino et al, 1996) and brain tumours (Langford et al, 1995). In the present study, the activity of this enzyme was demonstrated in more than 90% of colorectal carcinomas in line with previous studies (Chadeneau et al, 1995;Tahara et al, 1995b;Li et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Following the development by Kim et al (1994) of an extremely sensitive PCR-based assay, telomerase activity has been found in a large variety of solid tumours, including neuroblastomas (Hiyama et al, 1995a), lung carcinomas (Hiyama et al, 1995b), hepatomas (Tahara et al, 1995a), gastric and colon carcinomas (Chadeneau et al, 1995;Hiyama et al, 1995c;Tahara et al, 1995bLi et al, 1996, breast carcinomas (Hiyama et al, 1996;Sugino et al, 1996) and brain tumours (Langford et al, 1995). In the present study, the activity of this enzyme was demonstrated in more than 90% of colorectal carcinomas in line with previous studies (Chadeneau et al, 1995;Tahara et al, 1995b;Li et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, some studies have found correlations between telomerase activity and stage, traditional prognostic indicators, and clinical outcome in invasive breast cancer (Clark et al, 1997;Hoos et al, 1998). Other studies, however, failed to show a correlation between telomerase activity and prognostic factors or clinical outcome in breast cancer (Bednarek et al, 1997;Carey et al, 1998;Nawaz et al, 1997;Sugino et al, 1996;Tsao et al, 1997) and (Carey et al, in preparation, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…In our experiment, we have identified the telomerase activity in 293 cells and several human liver carcinoma cells respectively by telomerase TRAP-ELISA assay and non-radioisotopic silver staining telomeric repeat amplification protocol [24], [25]. The high sensitivity of the PCR-based TRAP assay has allowed the analysis of minimal tissue samples, such as fineneedle aspirates of the liver, breast and thyroid, cervical smears, oral washings, and urine [26][27][28][29][30][31]. In some experiments the sensitivity and specificity of the assay in detecting tumor cells has been compared with the gold standard, that is, cytology.…”
Section: Telomerase Assay and The Diagnosis Of Cancermentioning
confidence: 99%